2009
DOI: 10.1056/nejmoa0808991
|View full text |Cite|
|
Sign up to set email alerts
|

Mepolizumab and Exacerbations of Refractory Eosinophilic Asthma

Abstract: BACKGROUND-Exacerbations of asthma are associated with substantial morbidity and mortality and with considerable use of health care resources. Preventing exacerbations remains an important goal of therapy. There is evidence that eosinophilic inflammation of the airway is associated with the risk of exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,237
3
31

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,684 publications
(1,346 citation statements)
references
References 23 publications
40
1,237
3
31
Order By: Relevance
“…From a pragmatic, clinical perspective, phenotypic traits can be used in the daily clinical care to target-specific treatments: eosinophilia combined with exacerbations predicts effect of anti-IL5 [27] and patients with fixed airflow obstruction and exacerbations may benefit from tiotropium [28]. Furthermore, perennial allergic sensitization, airflow obstruction (FEV1 < 80%) and exacerbations predict effect of anti-IgE [5].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…From a pragmatic, clinical perspective, phenotypic traits can be used in the daily clinical care to target-specific treatments: eosinophilia combined with exacerbations predicts effect of anti-IL5 [27] and patients with fixed airflow obstruction and exacerbations may benefit from tiotropium [28]. Furthermore, perennial allergic sensitization, airflow obstruction (FEV1 < 80%) and exacerbations predict effect of anti-IgE [5].…”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…Second, the term eosinophilic asthma is used to describe a subphenotype of severe asthma, that is, asthma that is characterized by active eosinophilic inflammation, which remains uncontrolled and is associated with active eosinophilic inflammation despite the adequate use of high-dose corticosteroid treatment [14]. Wenzel and colleagues first described this 'eosinophil high' severe asthma phenotype when performing bronchial biopsies and showed that it was associated with airway remodeling and risk of near-fatal asthma attacks [15].…”
Section: How Is Eosinophilic Asthma Defined?mentioning
confidence: 99%
“…Однако, оказалось, что при исполь-зовании моноклональных антител, нейтрализующих IL5 (меполизумаб, mepolizumab), в сочетании с ингаляцион-ными ГКС лишь частично снижалось количество эози-Обзор литературы нофилов в дыхательных путях [30]. Клинически при при-менении меполизумаба отмечалось снижение частоты обострений БА, улучшение качества жизни без улучшения функции дыхательных путей и снижения гиперреактив-ности бронхов [31]. Апробация другого препарата, ней-трализующего IL5, -реслизумаба (reslizumab) в рандо-мизированном плацебоконтролируемом исследовании показала его положительное влияние на контроль астмы, документированный улучшением показателя ОФВ 1 , что, по мнению исследователей, подтверждало влияние эози-нофилов на течение БА и ее исходы [32].…”
Section: моноклональные антителаunclassified